Revealing the association between vitamin D metabolic pathway gene variants and lung cancer risk: a systematic review and meta-analysis - Elsalahaty, Mohamed I.; Alkafaas, Samar Sami; Bashir, Aya O.; El-Tarabily, Khaled A.; El-Saadony, Mohamed T.; Yousef, Eman H. (Frontiers in Genetics, 2024)
Lung cancer is a crucial global dilemma with more than one million deaths annually. Nevertheless, smoking is considered as the main etiology of disease, several genetic variants were associated with the disease.Alterations in the vitamin D pathway genes have also been studied with lung cancer; however, the findings are inconclusive Herein, we present a systematic review and meta-analysis of seven genes in this pathway, including CYP2R1, CYP27B1, CYP24A1, CYP3A4, CYP3A5, GC, and VDR. Four databases [PubMed, Scopus, Cochrane Library, and Web of Science database (WOS)] were searched. Consequently, 16 eligible case-control studies comprised 6206 lung cancer cases and 7272 healthy controls were obtained. The studies obtained were subjected to comprehensive data extraction, quality scoring, and pooled odds ratio with a 95% confidence interval to estimate the effect of each variant along with heterogeneity analysis and risk of bias assessment. Our meta-analysis revealed an association between CYP3A4*rs2740574 and lung cancer in the allelic, heterozygous, and dominant models. In addition, both VDR*Fok1 and VDR* Cdx-2 showed a protective role in lung cancer development in heterozygous and dominant models. Also, VDR*Taq1 showed a decreased risk of lung cancer in the allelic, homozygous, and recessive models. Similarly, VDR*BsmI had a positive effect on lung cancer risk when subjected to allelic and recessive models. Our meta-analysis revealed lack of association of CYP2R1*rs10741657, CYP27B1*rs3782130, CYP27B1*rs10877012, CYP24A1*rs6068816, CYP24A1*rs4809960, CYP3A5*rs776746, GC*rs7041, GC*rs4588, VDR*ApaI with lung cancer. Our work revealed that CYP3A4 (rs2740574) can work as an independent risk factor for lung cancer, a conclusion that aid in more personalized medicine for lung cancer management, while further assessment for genetic variants of CYP3A4, CYP27B1, CYP24A1, GC and VDR is still required to address more robust evidence.